2004
DOI: 10.1111/j.1067-1927.2004.12602.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vacuum‐assisted closure therapy on inguinal wound edge microvascular blood flow

Abstract: Vacuum-assisted closure (VAC) therapy has been shown to facilitate wound healing. Data on the mechanisms are scarce, although beneficial effects on blood flow and granulation tissue formation have been presented. In the current study, laser Doppler was used to measure microvascular blood flow to an inguinal wound in pigs during VAC therapy (-50 to -200 mmHg), including consideration of the different tissue types and the distance from the wound edge. VAC treatment induced an increase in microvascular blood flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
213
2
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(229 citation statements)
references
References 17 publications
8
213
2
6
Order By: Relevance
“…[6][7][8][9][10][11][12] In an experimental study conducted on rabbits, it was found that NPWT increased the blood circulation in the wounds by increasing the capillary calibre and blood volume and by stimulating angiogenesis. Further, it narrowed endothelial spaces and restored the integrity of capillary basement membranes causing a decrease in the permeability of blood vessels and wound oedema by removing excessive fluid from the wound bed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11][12] In an experimental study conducted on rabbits, it was found that NPWT increased the blood circulation in the wounds by increasing the capillary calibre and blood volume and by stimulating angiogenesis. Further, it narrowed endothelial spaces and restored the integrity of capillary basement membranes causing a decrease in the permeability of blood vessels and wound oedema by removing excessive fluid from the wound bed.…”
Section: Discussionmentioning
confidence: 99%
“…A low negative pressure during treatment may be beneficial, especially in soft tissue, to minimize possible ischemic effects. 11 The application of micromechanical forces through NPWT may be a useful method with which to stimulate wound healing through promotion of cell division, angiogenesis, and local elaboration of growth factors. 12 The application of sub atmospheric pressure alters the cytoskeleton of the cells in the wound bed, triggering a cascade of intracellular signals that increases the rate of cell division and subsequent formation of granulation tissue.…”
Section: Discussionmentioning
confidence: 99%
“…A later study used laser Doppler to measure blood flow during NPWT. This study suggested that optimal negative pressures were closer to 100 mmHg for muscular tissue and 75 mmHg for subcutaneous tissue [5]. It has also been suggested that intermittent negative pressure may improve blood flow as compared to continuous negative pressure.…”
Section: Introductionmentioning
confidence: 74%
“…183 Mechanisms that can be attributed to the benefits of TNP therapy have been investigated in basic research. The best described mechanisms are an increase in blood flow, 182,184 the promotion of angiogenesis, 185 and granulation tissue formation. 186 Moreover, the local negative pressure induces deformation of ECM and generates microstrain on cells, which can promote cell proliferation and migration.…”
Section: Biophysical Cuesmentioning
confidence: 99%